S45 VISTA expression in malignant pleural mesothelioma. (12th November 2019) - Rooney, C; Nixon, C; Blyth, K; Sethi, T; Murphy, D; McCaughan, F
Abstract : Introduction and objectives: Malignant pleural mesothelioma (MPM) pathogenesis is strongly influenced by the tumour microenvironment, supporting a role for immune checkpoint inhibition as a therapy. Only a small proportion of MPM patients benefit from checkpoint blockade and predictors of response are ambiguous. V-domain Ig suppressor of T cell activation (VISTA) is a novel negative checkpoint regulator, recently reported as highly expressed in a TCGA cohort of MPM. It is a PD-1 homolog thought to have similar immune restraining effects on T cells. Unusually, in MPM it is expressed on tumour cells and infiltrating immune cells. Clinical trials are already underway investigating VISTA inhibition in MPM. However there is no published data examining VISTA expression and clinical outcomes; thus we sought to determine the impact of VISTA expression on survival in 'all-comer' patients with MPM. Methods: Tissue microarray blocks from 161 MPM patients of all histological subtypes were obtained from MesobanK (Papworth Hospital). VISTA, CD8, CD163 and CD68 immunohistochemical staining was performed. Kaplan–Meier survival curves were used to estimate survival on the basis of levels of VISTA and other immune cells and were compared with the log-rank test. Cutoff values to define subgroups were the 25th or 50th percentile, i.e. the top 25th or 50th percentile was defined as high level and all others were defined as low level. Results: VISTA expression was detected in all MPM cases (n=160), comprising epithelioid (n=101), biphasic (n=38) and sarcomatoid (n=21). VISTA positivity was demonstrated in both tumour and immune cells. Kaplan-Meier curves demonstrated that patients with overall VISTA 'high' staining showed prolonged median survival than those with VISTA 'low' expression in all histological subtypes (916.5 days vs 274 days, p<0.0001). Immune infiltrating cell populations were quantified: CD163 'high' populations were associated with a poorer median survival; however there was no significant correlation between VISTA, CD8+, CD163, and CD68 status and survival outcome. Conclusions: To our knowledge this is the first study to analyse VISTA protein expression in a large cohort of MPM patients. We found that median survival is significantly higher in VISTA-'high' cohorts and is not influenced by CD8+ or macrophage status. Further studies should explore the mechanisms of VISTA effect in the context of tumour/stromal immunity in MPM.